THE ROLE OF SUPPORTIVE LEADERSHIP ON HEAD PERFORMANCE OF EDUCATION SECTOR IN INDONESIA - Nurul WAHIDA; Ihsana El KHULUQO; Fetrimen FETRIMEN (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2020)
In implementing the management of the institution requires decisiveness leadership and responsibility in improving the performance of members in order. In district education office there are some factors supportive leadership means improving the performance of members to improve the quality of Section Chief of District Education Office.The study is aimed at getting empirical answer about direct and indirect influence of supportive leadership on performance of Section Chief of District Education Office. Approach and method of this research is quantitative and descriptive correlation analysis while the model to complete this research is pathway analysis model. Sampling is done with simple random sampling of 30 Section Chiefs of District Education Office of 42 Population Districts. The results showed that supportive leadership has positive direct influence on performance. In conclusion supportive leadership have direct positive influence on performance of Chief of District Education Office.